Analysis of Extent of Deformation Range and Failure Characteristics of Rocks Surrounding a Tunnel Crossing Fault Zone Based on FDEM - Guo Xiaoxiong; Wang Ning; Xu Xueliang; Ye Zihui (Advances in Civil Engineering)
The combined finite-discrete element method (FDEM) and laboratory test were selected to study the extent of deformation range and time-dependent deformation of surrounding rock during tunnel excavation without support in a fault-crossing tunnel project. FDEM was found to accurately reflect the deformation and failure characteristics of different surrounding rocks during stress release, including conjugate shear and extrusion. Analysis of the results showed that the disturbance range of surrounding rocks could reach 1.5 to 2.5 times the tunnel diameter when crossing the fault zone. The rock surrounding the tunnel was found to incur significant conjugate shear deformation and extrusion deformation: conjugate shear deformation was identified as dominant in the deep rock mass, whereas extrusion deformation prevailed in the rock mass near the cave wall. The conjugate shear distribution was represented as a spiral line of deformation circling around the tunnel section, with an elliptical main deformation zone with its long axis parallel to the fault plane. Compared with the findings when crossing the intact rock mass, the deformation of the surrounding rocks when crossing the fault zone was characterized by rapid development, deep expansion area, and large deformation. The study conclusions were that supporting bolts and steel arches should be implemented timely when excavating fault zones and that both lithology and optimal construction timing were essential considerations in determining the length of the supporting bolts.